2020
DOI: 10.1038/s41467-020-19933-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy induces dynamic immune responses in breast cancers that impact treatment outcome

Abstract: To elucidate the effects of neoadjuvant chemotherapy (NAC), we conduct whole transcriptome profiling coupled with histopathology analyses of a longitudinal breast cancer cohort of 146 patients including 110 pairs of serial tumor biopsies collected before treatment, after the first cycle of treatment and at the time of surgery. Here, we show that cytotoxic chemotherapies induce dynamic changes in the tumor immune microenvironment that vary by subtype and pathologic response. Just one cycle of treatment induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 61 publications
5
117
0
Order By: Relevance
“…on June 27, 2021. © 2021 American Association for Cancer cancerdiscovery.aacrjournals.org Downloaded from biopsies, such as in breast cancer, where the tumor immune microenvironment was assessed in samples collected before treatment, after the first cycle of neoadjuvant chemotherapy, and at the time of surgery (296). Interestingly, this longitudinal study revealed that the on-treatment immune response was more predictive of treatment outcome compared with the paired baseline samples (296), supporting the inclusion of these types of dynamic real-time analyses in clinical trials wherever possible.…”
Section: Discussionmentioning
confidence: 99%
“…on June 27, 2021. © 2021 American Association for Cancer cancerdiscovery.aacrjournals.org Downloaded from biopsies, such as in breast cancer, where the tumor immune microenvironment was assessed in samples collected before treatment, after the first cycle of neoadjuvant chemotherapy, and at the time of surgery (296). Interestingly, this longitudinal study revealed that the on-treatment immune response was more predictive of treatment outcome compared with the paired baseline samples (296), supporting the inclusion of these types of dynamic real-time analyses in clinical trials wherever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy has long been considered immune suppressive; however, there is growing evidence that the e cacy of chemotherapy involves not only cell-intrinsic cytotoxic effects but also relies on the activation of antitumor immune responses (2). Recently, a study con rmed that after neoadjuvant chemotherapy for breast cancer, just one cycle of treatment can induce an immune stimulatory microenvironment and upregulation of in ammatory signatures (44). This nding may explain why the IVIM-DWI parameters follow the same trend in animal experiments and clinical trials.…”
Section: Discussionmentioning
confidence: 91%
“…Liu et al (2020a) reported the important roles of CTLA4 and PDCD1 in tumorigenesis, tumor immunity, and prognosis in Pan-Cancer. Park et al (2020) showed that CD274 expression on tumor cells was associated with prognosis in BRCA patients. Gheybi et al (2017) disclosed the involvement of CD19 in BRCA's immune response, linked with outcomes of BRCA patients.…”
Section: Discussionmentioning
confidence: 99%